Kepentingan Pembangunan Taman Rekreasi Awam di Parit Raja, Batu Pahat - Mohamad Nuramin Md Samsudin,; Masram, Haidaliza; Md Yassin, Azlina (Research in Management of Technology and Business, 2021)
The development of public recreation area is one of the facilities that need to be provided by the Local Authority (PBT) for the community of a city. Public recreation park is a recreational area that focuses on the society for recreation activities and relaxation either with family members, friends or individually.  The case study area, Parit Raja is one of the small towns under Batu Pahat Municipal Council, which has a growing population but does not have any recreational facilities provided specifically for its residents. Implementation issue in the development of public recreation park and its importance to the locals is seen as significant to justify the need for its provision in Parit Raja. In this regard, this study’s objectives are to identify current issues related to the development of public recreation park in Parit Raja and to study the importance of developing public recreation park for residents in Parit Raja, Batu Pahat, Johor. This study applied quantitative and qualitative approach through interview and survey as the instruments. This study identifies the current situation of recreational facilities in Parit Raja, especially in terms of preparation and issues regarding the development of public recreation park in the study area. Lastly it concluded the importance of providing reacreation area for the local community of Parit Raja.